2016
DOI: 10.1002/jmv.24472
|View full text |Cite
|
Sign up to set email alerts
|

Broncholaveolar lavage to detect cytomegalovirus infection, latency, and reactivation in immune competent hosts

Abstract: Roughly 1/3rd of immune competent patients will reactivate latent cytomegalovirus (CMV) during critical illness. There are no standard methods to detect reactivation, and some investigators have postulated that presence of DNA in BAL fluid is indicative of viral replication. To test this hypothesis, we used a murine model that allows inclusion of matched healthy controls which is not possible in human studies. BALB/c mice infected with Smith-murine CMV or PBS (mock) had BAL evaluated 7, 14, or 21 days after ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…Active CMV infection is a well-known opportunistic infection in immunocompromised patients, associated with a high viral load (Jaskula et al, 2009 ). CMV reactivation might also be related to the proinflammatory response associated with sepsis, as previously reported (von Muller et al, 2007 ; Cook and Limaye, 2012 ; Mansfield et al, 2016 ). Decrease in absolute number of all types of T cells has been reported in septic patients or septic shock, except the T regulatory cells.…”
Section: Discussionsupporting
confidence: 60%
“…Active CMV infection is a well-known opportunistic infection in immunocompromised patients, associated with a high viral load (Jaskula et al, 2009 ). CMV reactivation might also be related to the proinflammatory response associated with sepsis, as previously reported (von Muller et al, 2007 ; Cook and Limaye, 2012 ; Mansfield et al, 2016 ). Decrease in absolute number of all types of T cells has been reported in septic patients or septic shock, except the T regulatory cells.…”
Section: Discussionsupporting
confidence: 60%
“…It has been noted that critically ill patients in intensive care units often reactivate CMV, and this results in increased ventilation times and sometimes increased mortality rates (Kalil and Florescu 2011). Charles Cook (Boston, USA) presented an overview of the role CMV reactivation plays in aggravating disease in sepsis patients, presenting data from a murine model of sepsis which allows comparison with healthy controls (Mansfield et al 2016). The work presented showed that the lungs were an important site for CMV reactivation in these patients and that the presence of the virus alters the immune microenvironment, including changes to T cells and neutrophils in particular.…”
Section: Advances In Understanding Immune Evasion By CMVmentioning
confidence: 99%
“…Given the limits in the detection methodology, the CMV DNA detection of the patients here reported was not conducted with the materials from either the lung tissue or bronchoalveolar lavage, which were reported to have the highest frequency of detected CMV. 10,11 All the cases here analysed were DNA-negative for blood CMV detection but were seropositive. In particular, active CMV infection (acute infection or reactivation) was clinically defined in this paper as having fever and being responsive to ganciclovir.…”
Section: Discussionmentioning
confidence: 97%
“…lung tissue and bronchoalveolar lavage, which are actually unavailable in most cases) for CMV genome detection. 7,10,11 Accordingly, the therapeutic approach to CMV-associated ARF can only be based on comprehensive protocols, which include empirical antibiotics, high doses of steroids, pulse cyclophosphamide, intravenous immunoglobulin, mechanic ventilation and, more recently, rituximab. 12 In addition, there are reports about the application of ganciclovir in such conditions.…”
Section: Introductionmentioning
confidence: 99%